Optimization of asphalt mixture design based on the compressible packing model - Muhadeer, Yeermulati; Liang, Sun; Peiwen, Hao; Ningbo, Li; Junbiao, Wang (Frontiers in Materials, 2023)
Traditional design methods seldom consider accumulation properties, which influence the structure of asphalt mixtures. Therefore, this study is the first to put forward a modified compressible packing model. The filling characteristics of coarse aggregate were studied. Different matrix compaction indexes η and compaction indexes K were selected to study the influence of the modified compressible model on pavement performance. Design methods based on a 4% air void and minimum voids in mineral aggregate were compared through the volumetric parameters and pavement performance based on the modified compressible packing model. The asphalt mixture performances with three gradations were analyzed. The test results showed that as the matrix compaction index η decreased, the optimum asphalt content of both methods increased, while the VMA decreased. Finally, an optimized asphalt mixture design method based on the compressible packing model was proposed, which showed good prospects for application.